2015
DOI: 10.3109/14992027.2015.1046504
|View full text |Cite
|
Sign up to set email alerts
|

Adults with mild hearing impairment: Are we meeting the challenge?

Abstract: The development of appropriate audiological assessment in the clinic, and further evaluation of the real-world listening needs and performance of people with mild hearing impairment is required to provide a more effective pathway for this clinical population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 74 publications
2
32
0
1
Order By: Relevance
“…We defined mild HI to be a four-frequency average (4FAHL) between 20 and 40 dB HL, averaged across 500, 1000, 2000 and 4000 Hz. Our focus was on this population since we identified a paucity of evidence about the everyday difficulties of those with mild HI and they therefore present a clinical challenge in that it is not always clear whether or not they need intervention such as HAs (Timmer et al, 2015).…”
Section: The Use Of Ecological Momentary Assessment In Hearing Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined mild HI to be a four-frequency average (4FAHL) between 20 and 40 dB HL, averaged across 500, 1000, 2000 and 4000 Hz. Our focus was on this population since we identified a paucity of evidence about the everyday difficulties of those with mild HI and they therefore present a clinical challenge in that it is not always clear whether or not they need intervention such as HAs (Timmer et al, 2015).…”
Section: The Use Of Ecological Momentary Assessment In Hearing Researchmentioning
confidence: 99%
“…However, both methods have limitations. Objective measures, such as pure-tone audiometry and speech perception testing, allow for classification or quantification of hearing function however testing in the laboratory or clinical setting may have little ecological validity (Keidser, 2016;Smeds et al, 2015) and has only a moderate correlation, at best, with self-reported hearing difficulties (Lutman, 1991;Timmer et al, 2015). Therefore, self-reports measures are recommended to complement the commonly used audiological assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Sensorineural hearing loss (SNHL) is one of the most common long term disabilities in humans (Blackwell et al, 2014; Timmer et al, 2015). The vast majority of SNHL results from the loss of sensory hair cells (HCs), which, in mature mammalian cochleae, do not regenerate (McGill and Schuknecht, 1976; Soucek et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Noise‐induced hearing loss (NIHL) is one of the most common occupational illnesses in the United States, with nearly 22 million workers noise‐exposed workers in the United States . While hearing loss in itself is a disability, even workers with mild hearing loss experience reduced audibility (loudness) and dynamic range (range of softest to loudest sound capable of being heard) and often have difficulty understanding speech, especially in noisy environments . Preventing or reducing worker exposure to noise is imperative to preventing NIHL.…”
Section: Introductionmentioning
confidence: 99%